LATTICE STRAIN ANALYSIS OF TITANIUM ROD PROCESSED BY EQUAL-CHANNEL ANGULAR PRESSING (ECAP) WITH Bc ROUTE USING X-RAY DIFFRACTION LINE BROADENING ANALYSIS - Purawiardi, R. Ibrahim; Astawa, I Nyoman Gede Putrayasa (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2021)
Equal-channel angular pressing (ECAP) was one of severe plastic deformation method in order to increase the mechanical properties of solid metal without changing its dimension and without adding any alloy elements. The change of mechanical properties on ECAPed metals was caused by the change of lattice strain, so that the lattice strain investigation was recommended for evaluating ECAPed metals. In this study, pure titanium rod was treated by ECAP with Bc route and two passes. Before ECAPed, this titanium rod consisted of two lattice strains i.e. 0.001014 and 0.005241. After ECAPed, a lattice strain of 0.005241 reduces to 0.003205 and 0.003555 after first pass and reduces again to 0.002576 and 0.002647 after two passes. Meanwhile, a lattice strain of 0.001014 was annihilated after ECAP treatment. These results show that ECAP treatment can reduce and eliminate lattice strains on titanium rod. This study also shows that the reduction of lattice strains implicates to the increasing of its hardness value.